Determinants of Market Capitalization with Pofitability and Dividend Policy as Intervening Variables of State Owned Banks - I Wayan Budi Artha; Tri Widyastuti; Irvandi Gustari; Zulkifli; Bambang Purwoko (Dinasti Publisher, 2023)
The purpose of this study is to analyze and empirically prove the influence of the company's external and internal factors of market capitalization with profitability and dividend policy as intervening variables of State Owned Banks. The research period of 2011-2020, with the sampling technique is saturated sampling, in which all members of the population are used as samples. The analytical tool used is Structural Equation Modeling (SEM) supported by AMOS software. The results of the study show that the market capitalization of State Owned Banks is influenced by profitability, dividend policy, economic growth, BOPO and Loan at Risk (LAR). LAR besides having an effect on market capitalization, also has a direct effect on profitability and dividend policy. It is hoped that the results of this study can provide input for banks in maximizing the steps that must be taken to improve the company's performance and market capitalization.